Use of Cardiac Contractility Modulation as Bridge to Transplant in an Obese Patient With Advanced Heart Failure: A Case Report - Masarone, Daniele; Petraio, Andrea; Fiorentino, Antonio; Dellegrottaglie, Santo; Valente, Fabio; Ammendola, Ernesto; Nigro, Gerardo; Pacileo, Giuseppe (Frontiers in Cardiovascular Medicine, 2022)
Cardiac contractility modulation (CCM) is a novel device-based therapeutic approach in patients with heart failure with reduced ejection fraction (HFrEF). In randomized clinical trials and observational studies, CCM has been shown to result in improved exercise tolerance, improved quality of life, reverse left ventricular remodelling and reduced hospitalization in patients with HFrEF. In this case report, we describe for the first time the use of CCM as a “bridge to transplant” in a young obese patient with non-ischemic dilated cardiomyopathy with frequent hospitalizations for heart failure. The patient had a poor quality of life and frequent heart failure-related hospitalizations despite optimal medical therapy and, due to obesity, a suitable heart donor was unlikely to be identified in the short term and due to severe obesity risk of complications after implantation of a left ventricular assist device (LVAD) was very high.